2017
DOI: 10.4097/kjae.2017.70.4.426
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dexmedetomidine dose and plasma dexmedetomidine concentration in critically ill infants: a prospective observational cohort study

Abstract: BackgroundDexmedetomidine is a highly selective central α2-agonist used as a sedative in pediatric intensive care unit (PICU). However, little is known about the relationship between dexmedetomidine dose and its plasma concentration during long-term infusion. We have previously demonstrated that the sedative plasma dexmedetomidine concentration is moderately correlated with the administered dose in adults (r = 0.653, P = 0.001). We hypothesized that there would be a similar relationship between the sedative de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…These reports suggest that dexmedetomidine should be used with caution in patients with certain conditions in which sympathetic function is suppressed or parasympathetic function is enhanced. Fujita et al [ 19 ] reported that plasma dexmedetomidine concentration is correlated with the infusion dose in critically ill adult patients, but not in children < 2 years old admitted to the pediatric ICU [ 20 ]. These reports emphasize the need for close monitoring, individualized treatment, and dose adjustment to achieve the desired clinical response when administering dexmedetomidine.…”
mentioning
confidence: 99%
“…These reports suggest that dexmedetomidine should be used with caution in patients with certain conditions in which sympathetic function is suppressed or parasympathetic function is enhanced. Fujita et al [ 19 ] reported that plasma dexmedetomidine concentration is correlated with the infusion dose in critically ill adult patients, but not in children < 2 years old admitted to the pediatric ICU [ 20 ]. These reports emphasize the need for close monitoring, individualized treatment, and dose adjustment to achieve the desired clinical response when administering dexmedetomidine.…”
mentioning
confidence: 99%